Image interpretation performance: A longitudinal study from novice to professional. Issue 1 (February 2017) - Wright, C.; Reeves, P.
Abstract: Purpose: Universities need to deliver educational programmes that create radiography graduates who are ready and able to participate in abnormality detection schemes, ultimately delivering safe and reliable performance because junior doctors are exposed to the risk of misdiagnosis if unsupported by other healthcare professionals. Radiographers are ideally suited to this role having the responsibility for conducting the actual X-ray examination. Method: The image interpretation performance of one cohort of student radiographers was measured upon enrolment from UCAS in the first week of university education and then again prior to graduation using RadBench (n = 23). Results: The results identified that novices have a range of natural image interpretation skills; accuracy 35–85%, sensitivity 45–100%, specificity 15–85%, mean ROC 0.691. Graduates presented a narrower range; accuracy 60–90%, sensitivity 40–100%, specificity 60–90%, mean ROC 0.841. The positive shift in graduate mean accuracy (+16%) was driven by increases in specificity (+27%) rather than sensitivity (+5%). No statistically significant differences (ANOVA) could be found between age group, gender and previous education however trends were identified. 56.5% of the population (n = 13) met a benchmark accurate standard of 80%, including one graduate who met 90%. Conclusion: Image interpretation testing at the point of UCAS entry is a useful indicator of future performance and is a recommended factor for consideration as part of the selection process. Whilst image interpretation now forms an integral part of undergraduate radiography programmes, new graduates may not necessary possess the reliability in decision making to justify participation in abnormality detection schemes, highlighting the need for continuous professional development. Highlights: Some novices appear to have inherent skills in fracture identification. RadBench testing as part of the UCAS selection process provides a useful indication of future performance. Increase in specificity is the primary gain of university education in increasing accuracy. Radiography graduates may require further education in order to deliver reliable image interpretation decisions.